Modeling intensification decisions in the Kilombero Valley floodplain: A Bayesian belief network approach - Bisrat Haile Gebrekidan; Thomas Heckelei; Sebastian Rasch (Agricultural Economics, 2022)
The Kilombero Valley floodplain in Tanzania is a major agricultural area. Government initiatives and projects supported by international funding have long sought to boost productivity. Due to increasing population pressure, smallholder farmers are forced to increase their output. Nevertheless, the level of intensification is still lower than what is considered necessary to increase production and support smallholder livelihoods significantly. This article aims to better understand farmers' intensification choices and their interdependent determinants. We propose a novel modeling approach for identifying determinants of intensification and their interrelationships by combining a Bayesian belief network (BBN), experimental design, and multivariate regression trees. Our approach complements existing lower-dimensional statistical models by considering uncertainty and providing an easily updatable model structure. The BBN is constructed and calibrated using data from a survey of 304 farm households. Our findings show how the data-driven BBN approach can be used to identify variables that influence farmers' decision to choose one technique over another. Furthermore, the most important drivers vary widely, depending on the intensification options being considered.
Keywords: 330; agriculture; Bayesian belief network; intensification; Kilombero Valley; land use; regression trees; Tanzania